Epigenetic silencing of miR-493 increases the resistance to cisplatin in lung cancer by targeting tongue cancer resistance-related protein 1(TCRP1) - Yixue Gu; Zhijie Zhang; Jiang Yin; Jiahui Ye; Yin Song; Hao Liu; Yan Xiong; Minying Lu; Guopei Zheng; Zhimin He (Journal of Experimental & Clinical Cancer Research, 2017)
Abstract Background The potential mechanisms regarding how methylation of microRNA(miRNA) CpG Island could regulate cancer cell chemo-resistance remains unclear. This study aims to explore the epigenetic dysregulation mechanism of miRNA-493 and the ability to modulate lung cancer cell chemotherapy resistance. Methods Real-time quantitative PCR (qRT-PCR) and In situ hybridization (ISH) were used to analyze the expression of miR-493 in lung cancer cell lines and tumor tissue, respectively. Bisulfite sequencing PCR (BSP) was used to exam the promoter CpG Island of miR-493. The effect of miR-493 on chemosensitivity was evaluated by cell viability assays, apoptosis assays and in vivo experiment. The DNA damage was measured by γ-H2AX immunofluorescence. Luciferase reporter assay was used to assess the target genes of miR-493. Expression of target proteins and downstream molecules were analyzed by Western blot. Results miR-493 is silenced in resistant lung cancer cell due to the aberrant DNA methylation. Enforced expression of miR-493 in lung cancer cells promotes chemotherapy sensitivity to cisplatin through impairing the DNA damage repair and increasing the cells apoptosis in vitro and in vivo. Furthermore, we identify that TCRP1 is a direct functional target of miR-493. Ectopic expression of TCRP1 attenuated increased apoptosis in miR-493-overexpressing lung cancer cells upon cisplatin treatment. Meanwhile, miR-493 level is negatively correlated with TCRP1 expression in lung cancer patients and TCRP1 expression were correlated with poor survival. Conclusions Our results highlight that hyper-methylation of miR-493CpG island might play important roles in the development of lung cancer chemo-resistance by targeting TCRP1, which might be used as a potential therapeutic target in preventing the chemo-resistance of lung cancer.